Challenging the commodification of human rights: the case of the right to housing - Birchall, David (Santa Clara University's School of Law, 2021)
The profitability of commodified housing is driving extreme levels of corporate investment. To boost profits investors are exploiting “undervalued” low-income housing, evicting vulnerable individuals, hoarding land and charging exploitative fees. This is causing severe harm to individuals’ right to housing across the globe, including, inter alia, rapidly increasing prices and debt, increasing evictions, homelessness, and increased recourse to substandard accommodation. The harm is endemic, but the human rights response has been tepid. This paper argues that both state obligations and the content of the right to housing under the International Covenant on Economic, Social and Cultural Rights (ICESCR) can usefully address the problem. However, in communications with State Parties the Committee on Economic, Social and Cultural Rights (CESCR) addresses issues of commodification and affordability in vague terms that fail to generate meaningful obligations. The paper grounds the CESCR’s approach in theories of enforceability which argue that enforcement is more practicable when “clear violations” can be established. The CESCR offers clear statements of breach only when identifying explicitly wrongful practices, such as discriminatory laws. This approach, however, almost entirely occludes harm caused by the marketization of human rights. It skeletonizes the “protect” limb of state obligations, permits the long-term retrogression of affordability and enables the serious subsequent effects. The paper proposes that “clear violations” can be constructed from the results of, and laws constituting, harmful marketization. A three-stage process of identification of breach, standard-setting, and policy suggestions is recommended that can turn the long-term retrogression of access to housing into specific, measurable statements of violations and recommendations. This same approach is advocated for business responsibilities under the UN Guiding Principles on Business and Human Rights, with the content of these responsibilities also evaluated.